A compressive interface-capturing scheme for computation of compressible multi-fluid flows. (18th July 2017) - Ha, Cong-Tu; Kim, Dong-Hyun; Park, Warn-Gyu; Jung, Chul-Min
Highlights: A coupled dual-time stepping and compressive interface capturing scheme is presented. Interface flows are solved on curvilinear grids. Accuracy, efficiency, and robustness are assessed for various interface flows. Abstract: In this paper, a compressive high-resolution interface-capturing scheme is presented for the computation of compressible multi-fluid flows with high-density ratios and strong shocks. The proposed scheme is coupled with a preconditioned dual-time compressible mixture solver for robust and accurate computations over a wide range of Mach numbers. The scheme is simple and relatively easy to implement. It does not require any calculations for the interface curvature and the normal vector. The numerical approximations were implemented on general, structured grids using an implicit MUSCL upwind approach. Validation tests were conducted for a single reversible vortex, advection of an air-water interface, dam-break flow, and air shock-helium bubble interaction. Finally, a three-dimensional gas-lift flow is presented to demonstrate the capability of the present scheme for handling an interface with large jumps in pressure, temperature, and density.